2021
DOI: 10.1002/ejhf.2131
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium–glucose co‐transporter 2 inhibitors in patients with heart failure and type 2 diabetes mellitus: data from the Swedish Heart Failure Registry

Abstract: Use of sodium-glucose co-transporter 2 inhibitors (SGLT2i) in real-world heart failure (HF) is poorly characterised. In contemporary patients with HF and type 2 diabetes mellitus (T2DM) we assessed over time SGLT2i use, clinical characteristics and outcomes associated with SGLT2i use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
2
42
1
Order By: Relevance
“…The differential characteristics of patients treated by different care provider types have been described in previous studies. In general, HF patients treated by non-cardiologist have been observed to be older, more often female, with more comorbidities, higher EFs and lower use of HF therapy [2,3,6,11,12,17,18]. These studies reported unadjusted differences between patients treated by cardiologists vs noncardiologists, thus being subject to confounding.…”
Section: Associations Between Patient Characteristics and Type Of Carementioning
confidence: 99%
“…The differential characteristics of patients treated by different care provider types have been described in previous studies. In general, HF patients treated by non-cardiologist have been observed to be older, more often female, with more comorbidities, higher EFs and lower use of HF therapy [2,3,6,11,12,17,18]. These studies reported unadjusted differences between patients treated by cardiologists vs noncardiologists, thus being subject to confounding.…”
Section: Associations Between Patient Characteristics and Type Of Carementioning
confidence: 99%
“…Results were consistent across the broad spectrum of cardio‐renal‐metabolic risk, although those with established HF had the greatest absolute benefit 28 . SGLT2 inhibitors were administered to only 376 (5.5%) of 6805 patients with HF and type 2 diabetes included in the SwedeHF Registry with, however, increasing use over time, especially in young patients, with a history of ischaemic disease and normal renal function 29 . Their administration was associated with a 30% reduction of cardiovascular death/first HF hospitalization 29 .…”
Section: Medical Treatmentmentioning
confidence: 69%
“…SGLT2 inhibitors were administered to only 376 (5.5%) of 6805 patients with HF and type 2 diabetes included in the SwedeHF Registry with, however, increasing use over time, especially in young patients, with a history of ischaemic disease and normal renal function 29 . Their administration was associated with a 30% reduction of cardiovascular death/first HF hospitalization 29 . In a pre‐specified biomarker study from DECLARE‐TIMI 58, dapagliflozin reduced the composite risk of cardiovascular death or HF hospitalization irrespective of baseline N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) and high‐sensitivity troponin T (hsTnT) values.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Nonetheless, limitations of the current study should be recognized 9 . First, the observational nature of this analysis precludes definitive determination of cause–effect relationships.…”
Section: Figurementioning
confidence: 90%
“…11,12 Nonetheless, limitations of the current study should be recognized. 9 First, the observational nature of this analysis precludes definitive determination of cause-effect relationships. Despite rigorous statistical methods, residual or unmeasured confounding may contribute to the results seen here.…”
mentioning
confidence: 99%